2013
DOI: 10.1371/journal.pone.0078443
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Analysis of Hsp70 Inhibitors

Abstract: The molecular chaperones of the Hsp70 family have been recognized as targets for anti-cancer therapy. Since several paralogs of Hsp70 proteins exist in cytosol, endoplasmic reticulum and mitochondria, we investigated which isoform needs to be down-regulated for reducing viability of cancer cells. For two recently identified small molecule inhibitors, VER-155008 and 2-phenylethynesulfonamide (PES), which are proposed to target different sites in Hsp70s, we analyzed the molecular mode of action in vitro. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
177
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(189 citation statements)
references
References 58 publications
9
177
2
1
Order By: Relevance
“…8, eЈ and eЉ). To provide a functional test for involvement of Hsc70 in imatinib-induced TfR1 degradation, we utilized a small molecule ATP-derivative inhibitor of Hsc/Hsp70 chaperones (VER155008) that is well described to have antitumor properties (32). Importantly, we found that this inhibitor minimizes the imatinib-dependent TfR1 degradation by lysosomes.…”
Section: C-abl Regulates Tfr1 Endocytosismentioning
confidence: 99%
“…8, eЈ and eЉ). To provide a functional test for involvement of Hsc70 in imatinib-induced TfR1 degradation, we utilized a small molecule ATP-derivative inhibitor of Hsc/Hsp70 chaperones (VER155008) that is well described to have antitumor properties (32). Importantly, we found that this inhibitor minimizes the imatinib-dependent TfR1 degradation by lysosomes.…”
Section: C-abl Regulates Tfr1 Endocytosismentioning
confidence: 99%
“…To test this, first we applied to tumor cells before irradiation the small-molecule inhibitor VER155008, which inhibits the activity of both the induced and constitutive forms of Hsp70 (21,22). Tumor cell numbers after 72 hours were only slightly lower when VER155008 was applied to irradiated cells, presumably because cell proliferation was already slowed down by the irradiation.…”
Section: Hsp70 Inhibition Blocks Antigen Cross-presentationmentioning
confidence: 99%
“…Chaperone inhibitors are intended to block oncogenic or disease protein folding and function to sensitize cells to cellular stress generated by conventional chemotherapies (Neckers and Workman, 2012). HSP/C 70/90 are both attractive as therapeutic targets because they contain multiple sites amenable to drug targeting, including ATP cofactor-binding sites, client protein substrate sites, and protein-protein interfaces (PPIs), with cochaperones that facilitate client protein folding activity (Rérole et al, 2011;Assimon et al, 2013;Balaburski et al, 2013;Schlecht et al, 2013). Many HSP/C 90/70 inhibitors are indeed small molecule adenosine analogs that target the nucleotidebinding site (Chiosis et al, 2002;Dymock et al, 2004;Donnelly and Blagg, 2008;Williamson et al, 2009;Day et al, 2010;Budina-Kolomets et al, 2014).…”
Section: Therapeutic Chaperone Inhibition Is An Established Paradigmmentioning
confidence: 99%